Soil scarification does not affect the medium-term species composition of Norway spruce stands - Medicus, Thomas; Tischer, Alexander; Michalzik, Beate; Wagner, Kim; Bernhardt-Römermann, Markus (Frontiers in Forests and Global Change, 2025)
Soil scarification, which involves the disruption of the top layer of soil, is a common method utilized to promote the regeneration of tree species on clear-cut and calamity areas. In the context of adapting forests to become climate-resilient mixed species forests, this method could also be used to promote tree regeneration under intact canopies, either exclusively or in combination with direct seeding. However, evidence on the impact of this method on the composition of forest floor vegetation, including bryophytes, is lacking and needs to be investigated. This is of importance because the forest floor vegetation significantly contributes to species richness in temperate forests. To address how and to what extent soil scarification affects the forest floor species composition, we conducted a space-for-time-substitution study, creating a chronosequence spanning a 13-year period, to investigate the effect of soil scarification on forest floor vegetation in Norway spruce (Picea abies) stands in a lower montane forest in central Germany. Our results showed that soil scarifications were quickly recolonized by bryophyte species, whereas herbaceous species cover took around a decade to reach a similar level of establishment as the undisturbed forest floor. Species composition initially shifted in favor of early successional species. In the long term, however, the species composition converged back to the undisturbed state. Tree regeneration diversity especially benefitted from scarification, making it a viable method for intact forest stands, particularly given that it does not appear to exert any adverse effect on forest floor vegetation.